A Black Cohosh Extract Causes Hematologic and Biochemical Changes Consistent with a Functional Cobalamin Deficiency in Female B6C3F1/N Mice. (July 2017) - Cora, Michelle C.; Gwinn, William; Wilson, Ralph; King, Debra; Waidyanatha, Suramya; Kissling, Grace E.; Brar, Sukhdev S.; Olivera, Dorian; Blystone, Chad; Travlos, Greg
Black cohosh rhizome, available as a dietary supplement, is most commonly marketed as a remedy for dysmenorrhea and menopausal symptoms. A previous subchronic toxicity study of black cohosh dried ethanolic extract (BCE) in female mice revealed a dose-dependent ineffective erythropoiesis with a macrocytosis consistent with the condition known as megaloblastic anemia. The purpose of this study was to investigate potential mechanisms by which BCE induces these particular hematological changes. B6C3F1/N female mice (32/group) were exposed by gavage to vehicle or 1, 000 mg/kg BCE for 92 days. Blood samples were analyzed for hematology, renal and hepatic clinical chemistry, serum folate and cobalamin, red blood cell (RBC) folate, and plasma homocysteine and methylmalonic acid (MMA). Folate levels were measured in liver and kidney. Hematological changes included decreased RBC count; increased mean corpuscular volume; and decreased reticulocyte, white blood cell, neutrophil, and lymphocyte counts. Blood smear evaluation revealed increased Howell–Jolly bodies and occasional basophilic stippling in treated animals. Plasma homocysteine and MMA concentrations were increased in treated animals. Under the conditions of our study, BCE administration caused hematological and clinical chemistry changes consistent with a functional cobalamin, and possibly folate, deficiency. Further studies are needed to elucidate the mechanism by which BCE causes increases in homocysteine and MMA.